Examining Student Plate Waste Following a Conversion From Pre-packaged to Lunches Prepared On-Site: A Longitudinal Cohort Study. (14th June 2022) - Richardson, Scott; Cohen, Juliana; Rimm, Eric; Gortmaker, Steven
Abstract: Objectives: Subsidized meals provided through the National School Breakfast and Lunch programs are an important source of daily nutrition for millions of students across the United States. Aging school infrastructure has led some districts to rely on pre-packaged meals to feed students over the past few decades. It is unclear how investments in infrastructure upgrades that would enable on-site scratch cooking in schools might influence student selection and consumption of school meals. The aim of this study was to assess changes in student selection and consumption of school lunches following a conversion from pre-packaged meals to lunches prepared on-site, the introduction of salad bars on the lunch line, and removal of flavored milk offerings. Methods: Quasi-experimental difference-in-difference analysis of pre/post direct observation weighed plate waste measurements collected in Fall 2018 and Spring 2019 from 595 3rd-5th graders at eight elementary schools (four intervention, four controls) in a large urban school district in New England. Descriptive statistics and mixed-model linear regressions controlling for grade, sex, intervention, and observations nested within individual were used to examine changes in meal component selection and consumption. Results: Student selection and consumption of vegetables increased by 31 grams (95%CI 18g – 43g) (equivalent to ∼3.25 carrot sticks or grape tomatoes) in intervention schools relative to controls, while student selection and consumption of milk decreased by 46g (95%CI 18g – 43g) (∼1/5 of an 8 ounce milk carton). Entrée and fruit selection and consumption did not change significantly. Conclusions: Removal of flavored milk may lead to an initial decline in milk selection and consumption. Increased offerings of fresh unpackaged vegetables can increase student acceptance and consumption. Funding Sources: T32 HL098048/HL/NHLBI NIH HHS/United States.